Percepção e atitude de produtores de leite de Minas Gerais de diferentes extratos de produção em relação ao Boophilus microplus - Christiane Maria Barcellos Magalhaes da Rocha (2005)
Milk producers (n = 193) from three counties (Lavras, steps, and Divinópolis) Minas Gerais state were interviewed to evaluate their perception and attitude control of Boophilus microplus. The information obtained was analyzed by three paths. First, the data underwent a qualitative analysis to profile the knowledge of these. Data were also submitted to an'slise multidimensional principal component and regression using as dependent variables, frequency of use of acaricides and perceptional indicators and attitude of the producers. The perception and attitude about the cattle tick were similar between the producers, and most do not have the basic knowledge about the biology and control of ticks and products by applying the pump and without costal defined technical criteria. Some results of principal component analysis were: (I) negative correlation between education and frequency of application of tick in cattle, (II) a positive correlation between milk production, quality of insecticide application equipment and technological level of the farm, (III ) positive correlation between education, technological level of the farm and perceptional on the cattle tick. Regression analysis showed that the best equipment and the use of acaricide concentration in a period of years reduce the frequency of acaricide applications in livestock. Owners of larger farms technological level, have better attitudes and perceptions about the tick. Test for efficiency of tick dip for ticks on 17 farms. Baiza correlations between the efficiencies of chemical groups of acaricides suggest similar differences in their qualities